Functions of MDMX in the Modulation of the p53-Response - Lenos, Kristiaan (Hindawi Publishing Corporation, 2011)
The MDM family proteins MDM2 and MDMX are two critical regulators of the p53 tumor suppressor protein. Expression of both proteins is necessary for allowing the embryonal development by keeping the activity of p53 in check. Upon stresses that need to activate p53 to perform its function as guardian of the genome, p53 has to be liberated from these two inhibitors. In this review, we will discuss the various mechanisms by which MDMX protein levels are downregulated upon various types of stress, including posttranslational modifications of the MDMX protein and the regulation of mdmx mRNA expression, including alternative splicing. In addition, the putative function(s) of the described MDMX splice variants, particularly in tumor development, will be discussed. Lastly, in contrast to common belief, we have recently shown the existence of a p53-MDMX feedback loop, which is important for dampening the p53-response at later phases after genotoxic stress.